Propuesta de un marco regulatorio para la concesión de títulos habilitantes a operadores móviles virtuales en el Ecuador. - Guambuguete Loza, Elizabeth de los Angeles (2018)
The present project intends to develop a regulation that allows regulating the different activities that an MVNO will develop in Ecuador, its duties and rights with respect to the host operator, in addition to the minimum conditions that must be included in the negotiation contract between the Network Operator and the OMV together with the sanctions to which it may be subject for breach of any of them. The Mobile Virtual Operators by their abbreviations OMV were created as commercial figures which exist in several European countries can be highlighted to the United Kingdom where the birth of this class of operators had the purpose of generating more competition with mobile operators applying for this class of services before and after the application of the regulation of an MVNO, this way allows the negotiation between the agents that act in the market to obtain the access to the use of the infrastructure that allows to offer the service to the operators, the Government only reserves the right to act only when one of the agents violates the principles of free competition, under this principle of regulation it is possible to make viable this kind of business in the country as it is being done in other countries. With the described and thinking that there will be a development of this technology in Ecuador, it is justified to generate a regulation framework in the telecommunications sector for this business turn, based on the current regulatory framework for mobile operators in Ecuador.